Bandits in Print "The Water Margin" and the Transformations of the Chinese Novel - Gregory, Scott W. (Cornell University Press, 2023)
Bandits in Print examines the world of print in early modern China, focusing on the classic novel The Water Margin (Shuihu zhuan). Depending on which edition a reader happened upon, The Water Margin could offer vastly different experiences, a characteristic of the early modern Chinese novel genre and the shifting print culture of the era. Scott W. Gregory argues that the traditional novel is best understood as a phenomenon of print. He traces the ways in which this particularly influential novel was adapted and altered in the early modern era as it crossed the boundaries of elite and popular, private and commercial, and civil and martial. Moving away from ultimately unanswerable questions about authorship and urtext, Gregory turns instead to the editor-publishers who shaped the novel by crafting their own print editions. By examining the novel in its various incarnations, Bandits in Print shows that print is not only a stabilizing force on literary texts; in particular circumstances and with particular genres, the print medium can be an agent of textual change.